Early cell response of osteogenic cells on differently modified implant surfaces: Sequences of cell proliferation, adherence and differentiation. Issue 3 (March 2018) - Blatt, Sebastian; Pabst, Andreas Max; Schiegnitz, Eik; Hosang, Marco; Ziebart, Thomas; Walter, Christian; Al-Nawas, Bilal; Klein, Marcus Oliver
Abstract: Objectives: Osseointegration of dental implants is a crucial prerequisite for long-term survival. Therefore, surface modifications are needed to interact with the extracellular environment and to trigger osteogenic cell responses such as cell proliferation, adherence, and differentiation. The purpose of this study was to investigate different surface modifications in vitro over 2 weeks. Materials and methods: Commercially available cells from a human osteogenic cell line (HHOB-c) were cultivated on the following surfaces: titanium with smooth surfaces (polished titanium (P), machined titanium (M), polyetheretherketone (Peek)), titanium with rough and hydrophilised surfaces (acid etched titanium (A), sandblasted acid etched titanium (SA and SA2), sandblasted acid etched hydrophilised (SAH), titanium plasma painted titanium (TPS)), titanium with calcium phosphate-containing surfaces (titanium plasma painted calcium phosphate modified titanium (TPS-CaP), sandblasted calcium phosphate modified titanium (S-CaP), sandblasted acid etched calcium phosphate modified titanium (SA-CaP)), and zirconium-oxide (yttrium amplified zirconium (Z), yttrium amplified Ca 2+ delivering zirconium (Z-Ca)). Tissue culture polystyrene (TCPS) served as a control. Cell count was assessed after 24 h, 48 h, 72 h, 7 d, and 14 d; osteogenic cell adherence and differentiation were analysed by using cellular Quantitative Immuno-Cytochemistry (QIC) assay for alkaline phosphatase (AP), osteocalcin (OC), integrin alpha V (ITGAV), and talin (T). Results: All tested surfaces showed a positive influence on the differentiation and adherence of osteogenic cells, especially P, M, A, TCPS, and Peek. After 48 h, the surfaces M, SA and SAH had induced a positive influence on adherence, whereas SA2, SA, and SAH triggered proliferation after 14 d. Conclusions: Rough and hydrophilised surface modifications, such as SAH, trigger osteogenic cell responses. These in vitro results highlight the potential use of SAH surface modifications of dental implants and indicate further clinical studies are warranted.